The moral life of epinephrine in the United States (Medicine Anthropology Theory, 2016)
This paper follows the ‘moral life’ of epinephrine auto-injectors, devices that people with food allergies and their caretakers use to administer emergency medication to stop serious allergic reactions, in the United States. These devices are potent signifiers of the seemingly precarious nature of life with food allergies. I follow auto-injectors from their social birth as a commodity object, through how they structure doctor-patient interactions and parenting, to the ways that parents and illness advocates talk about their life-saving properties. At every step of the way, their significance is influenced by the political-economic context of health care in the United States, which places significant burdens of financial cost and responsibility for deciding what constitutes ‘good’ care upon individual patients and caretakers. The moral life of epinephrine serves as a model for thinking about how medical devices take on meaning that is at once practical, moral, and economic as they circulate through manufacturing and distribution channels and into the lives and social worlds of users.